2011
DOI: 10.1093/heapol/czr014
|View full text |Cite
|
Sign up to set email alerts
|

Integrating microfinance and health strategies: examining the evidence to inform policy and practice

Abstract: Worldwide, current public health programmes and health systems are proving to be inadequate to meet population needs. The microfinance sector offers an underutilized opportunity for delivery of health-related services to many hard-to-reach populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 23 publications
1
84
0
Order By: Relevance
“…In addition to the resources provided by the CRS, promoting partnerships with microcredit organisations may decrease both internal and structural barriers by providing opportunity for income generation, employment, and social cohesion, all of which could improve the resettlement process. For decades, international microcredit organisations have simultaneously incorporated health education and health care access into their program designs (Leatherman et al, 2012). Members of the sewing group at the CRS may be primed to transition into microcredit businesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the resources provided by the CRS, promoting partnerships with microcredit organisations may decrease both internal and structural barriers by providing opportunity for income generation, employment, and social cohesion, all of which could improve the resettlement process. For decades, international microcredit organisations have simultaneously incorporated health education and health care access into their program designs (Leatherman et al, 2012). Members of the sewing group at the CRS may be primed to transition into microcredit businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Microcredit is designed to improve income and build assets, thus decreasing economic inequalities and enhancing capacity for success. Leatherman, Metcalfe, Geissler, and Dunford (2012) have suggested that microcredit is an underutilised opportunity to improve health disparities. Having an accessible income-generating activity (IGA) can be both a protective health factor and socially empowering during the resettlement process.…”
Section: Introductionmentioning
confidence: 99%
“…3 Overall, these studies show that (1) microfinance can help with the dissemination of health knowledge to loan recipients, and (2) microloans are feasible to deliver in the health care setting. 3 …”
Section: International Issues: Microfinance In Neurologic Disordersmentioning
confidence: 82%
“…MFIs can provide financial support while offering patient education, enabling access to health care, and building community capacity for health services and infrastructure. 3 A recent review summarizes studies that evaluate the effectiveness of MFIs in improving health care, with various levels of evidence ranging from observational studies to randomized trials. 3 Overall, these studies show that (1) microfinance can help with the dissemination of health knowledge to loan recipients, and (2) microloans are feasible to deliver in the health care setting.…”
Section: International Issues: Microfinance In Neurologic Disordersmentioning
confidence: 99%
See 1 more Smart Citation